Determinants of public indebtedness in European Union countries - Janusz Kudła (e-Finanse: Financial Internet Quarterly, 2018)
The paper strives to determine the impact of fiscal variables on factors determining the dynamics of public debt in European Union countries. Based on the literature, the dynamics of public debt are determined by changes of three elements: the primary balance, interest-rate-growth-differential and the change of government assets. Therefore, it seems reasonable to estimate the dynamics of these three values to find the variables crucial for limiting the growth of public debt. Three groups of dynamic panel regressions were estimated based on the one-step Generalized Method of Moments. The data was collected for the 1995-2015 period for 27 EU countries. Dependent variables included: primary balance, interest-rate-growth-differential and change of government assets. Independent variables consisted of: interest payable to GDP ratio, unemployment rate, squared unemployment rate, FDI stock to GDP, net FDI inflow to GDP, general government expenditures to GDP, share of social security expenditures and openness of the economy measured by the ratio of export and import to GDP. On the basis of statistical data, three components of debt changes were distinguished, and estimations of the dynamic panel regressions were applied to find the impact of independent variables. According to the basic models, the primary balance is lower for: countries with higher unemployment, greater FDI stock and higher general government expenditures.
Keywords: H71; H26; H72; 330; public debt dynamics; interest-rate-growth-differential; primary balance